Industry 4.0 Readiness and Roadmap in Food Industry: Insights from Indonesian Manufacturing Enterprises Using Explanatory Sequential Mixed-Method Design - Iman Rahmatulloh; Siska Noviaristanti; Muhammad Awaluddin (Green Publisher Indonesia, 2024)
The paper aims to understand the current readiness level of Industry 4.0 in the food industry. Furthermore, the study explores the prioritized Industry 4.0 dimensions and initiatives needed to improve the readiness level. The study uses an explanatory sequential mixed-method design. In the quantitative phase, the Industry 4.0 readiness assessment was conducted using the Smart Industry Readiness Index framework. The quantitative study further explores the prioritized dimensions using The Prioritization Matrix framework. In the qualitative phase, interviews with industry practitioners from the participating companies were conducted to gain more understanding and propose the conceptual roadmap. The study found that the Indonesian food industry has a better average readiness than the global average but significantly lower than the best-in-class manufacturers. Vertical Integration, Shop Floor Intelligence, Shop Floor Automation, and Workforce Learning & Development are four priority dimensions to increase the readiness level in the food industry. A conceptual roadmap was proposed to improve the readiness index based on the strategic planning horizon, prioritized dimensions, and initiatives identified from interview results. The results of this study would provide an additional reference for applying explanatory sequential mixed-method design. The prioritized dimensions found would also benefit other researchers in the development of the readiness or maturity model. This paper provides a deeper understanding of Industry 4.0 readiness, the prioritized dimensions, and related improvement initiatives to propose the strategic roadmap for the food industry by utilizing explanatory sequential mixed-method design.